A Schema Theory Analysis of The Game Character Eunie From ‘Xenoblade Chronicles 3’ - Agung Olaf Ridho Rambe; Rahmadsyah Rangkuti (Jurnal Arbitrer, 2023)
This article examines the activation of a schema based on the game, the realization of the Schema Theory in the game character named Eunie, and the proof of Eunie’s status as the primary character in the game. The study analyzes the factors that trigger the activation of a schema and how it relates to the game’s structure. It explores how the Schema Theory manifests in the game character Eunie, highlighting her role as the central character. The research provides evidence to support the claim that Eunie is, in fact, the main character in the game. The study at hand utilizes the Schema Theory components introduced by J. Piaget to investigate the research on Cognitive Stylistics. In order to characterize the themes that are realized in the game Xenoblade Chronicles 3, the research is carried out utilizing a qualitative descriptive design with case study. The research focuses on a schema that influences how people see their surroundings and the world around them. It suggests that in order for a player to completely understand an idea or a tale from the game, that player’s prior knowledge is necessary. There are seven components in the schema theory that must be outlined: Figure and Ground, Prototypicality, Resonance and Ambience, Metaphor and Framing, Simulation and Projection, Mind-Modeling, and Text-Worlds. The result emphasized the importance of schemas in aiding readers to interpret the game’s world and characters’ accents. This study highlights the significance of Schema Theory in Cognitive Stylistics as a valuable framework for comprehending character development and literary analysis in video games.